2016
DOI: 10.11622/smedj.2016006
|View full text |Cite
|
Sign up to set email alerts
|

A review of stab wound injuries at a tertiary trauma centre in Singapore: are self-inflicted ones less severe

Abstract: , MBBS, FAMS INTRODUCTION In Singapore, as strict laws are a strong deterrent against armed violence, little is known about the epidemiology of penetrating stab wound injuries. Our study aimed to investigate the epidemiology of stab wound injuries at a major trauma centre in Singapore and determine if there was a difference in severity between self-inflicted stab wound (SI) injuries and those inflicted by others (IO). METHODSWe retrospectively reviewed all penetrating injuries at Tan Tock Seng Hospital, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…In our case, 77.5% of the cases of abdominal trauma were stab wounds, with a total of 231 patients in 2 years, demonstrating the high volume of patients who are managed surgically in urgent scenarios. In the same way that Leow et al data (15) suggested, our data imply that young men are more likely to participate in activities that result in penetrating abdominal injuries. This is due to the fact that male patients made up the vast majority of the population in the vast majority of cases, with a median age of 28 IQR (22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our case, 77.5% of the cases of abdominal trauma were stab wounds, with a total of 231 patients in 2 years, demonstrating the high volume of patients who are managed surgically in urgent scenarios. In the same way that Leow et al data (15) suggested, our data imply that young men are more likely to participate in activities that result in penetrating abdominal injuries. This is due to the fact that male patients made up the vast majority of the population in the vast majority of cases, with a median age of 28 IQR (22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 83%
“…These injuries are usually the result of the application of a mechanical force on a focal area, which may varies depending on the force that is transmitted (14). Similarly, injuries are caused by a stab or gunshot, most often involving thoracic and abdominal trauma (15). Leow et al (15) published a study that included 149 stab wounds over a 5-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of sharp wounds tends to be worse when inflicted by others, compared to that of self-inflicted wounds. 10 Previous studies have reported that computed tomography is effective for the diagnosis of the severity or indication of surgery for penetrating neck trauma. 11 It is extremely difficult to accurately diagnose the depth or severity in field settings; thus, a more severe triage category must be assigned to casualties on the field for safety reasons.…”
Section: Discussionmentioning
confidence: 99%